Political cycles in physician employment: A case of Japanese local public hospitals. (November 2018) - Takaku, Reo; Bessho, Shun-ichiro
Abstract: A shortage of physicians in local public hospitals is often a heated political issue. When local politicians have the authority to intervene in the management of a public hospital, they may increase the employment of physicians during election years in order to alleviate the shortage. We test this hypothesis empirically using a census of city hospitals in Japan from 2002 to 2011 (N = 4583). Our results support the hypothesis that the number of physicians increases in election years. This effect is stronger in cities with a greater population of elderly residents. We also find that physicians tend to come from university hospitals in the same region. Overall, this paper provides direct evidence of political intervention on physician employment. Highlights: A shortage of hospital physicians was a heated political issue in Japan. We examine how the timing of mayoral elections affected local public hospitals in Japan. The number of physicians increased in election years. The effect was stronger in cities with a greater population of elderly residents. We find that physicians came from university hospitals in the same region.